AVIAN FAUNA OF SUMMER HILL, SHIMLA – HIMACHAL PRADESH - A. N. KULKARNI,; P. GOSWAMI, (The Bioscan, 2011)
The capital of Himachal Pradesh, Shimla is located in the mid hills of Western Himalaya and was developed from a village as a summer capital of British India surrounded by thick forest of pine, oak, rhododendron and tall cedar trees. Shimla is famous for biodiversity of birds. For the study of avian fauna summer hill station was selected. The study was conducted from 6-9th May 2008. During the study 31 species of birds belonging to 21 families were recorded. Dominant birds of this region are House Sparrow, Rock Pigeon, Myna, Dipper and Himalayan Bulbuls.